2016
DOI: 10.1186/s13071-016-1910-x
|View full text |Cite
|
Sign up to set email alerts
|

New epidemiological aspects of visceral and cutaneous leishmaniasis in Taza, Morocco

Abstract: BackgroundLeishmaniasis is considered among the main endemic diseases in Morocco. However, further knowledge about epidemiological aspects of this disease is needed in several provinces to plan control and preventive strategies to tackle the disease. The present study aims to determine the epidemiological aspect of cutaneous and visceral leishmaniasis in Taza Province from 2007–2014 and to identify the circulating species in this province.ResultsThe temporal study from 2007 to 2014 showed that the number of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…Our result is consistent with many studies; in Algeria (189 men and 197 women; sex ratio F/M: 1.04) [11]. Also in Taza, Morocco which found a slight in the CL prevalence between genders with predominance of CL in females (57 vs. 43% for men; sex-ratio F/M = 1.32) [12] and in another study, 44% male and 56% female patients were affected by CL [13].…”
Section: Cutaneous Leishmaniasis: Endemic Regions and Epidemiologicalsupporting
confidence: 93%
See 2 more Smart Citations
“…Our result is consistent with many studies; in Algeria (189 men and 197 women; sex ratio F/M: 1.04) [11]. Also in Taza, Morocco which found a slight in the CL prevalence between genders with predominance of CL in females (57 vs. 43% for men; sex-ratio F/M = 1.32) [12] and in another study, 44% male and 56% female patients were affected by CL [13].…”
Section: Cutaneous Leishmaniasis: Endemic Regions and Epidemiologicalsupporting
confidence: 93%
“…The results found in Morocco showed that no age group was spared from leishmaniasis [12], in another study patients' ages varied from 1.25 to 70 years [13].…”
Section: Distribution Of CL By Agementioning
confidence: 84%
See 1 more Smart Citation
“…Some sporadic cases of CL due to Leishmania infantum have also been described. 2 , 3 Cutaneous leishmaniasis scars on the face can cause considerable psychosocial suffering. In young women in North Africa and the Middle East, social rejection, diminished marriage and employment prospects, and suicidal thoughts have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…In central Morocco, L. tropica is the only agent responsible for CL cases in certain provinces [23]. In others, this species has been isolated alongside a few cases of L. infantum [24,25]. However, at Southwest, L. tropica is the only prominent species [13,26].…”
Section: Introductionmentioning
confidence: 99%